Hubungan Kepribadian Big Five Terhadap Pembentukan Organizational Citizenship Behaviour (OCB) Pegawai Pada PT Amarta Karya (Persero) Bekasi - Salwa Salwa; Wikansari Rinandita (JURNAL ILMIAH MANAJEMEN & BISNIS, 2017)
This research aimed to determine the relation  the Big Five Personality Dimension to Organizational Citizenship Behavior (OCB) employees of PT Amarta Karya (Persero) Bekasi..This Research used quantitative method. The measuring tool used in this research is a questionnaire divided into 2 scales those are, the personality scale consists of 35 points statements and OCB scale consists of 20 items statemenst. The number of respondents in this research is 30 employee. This research used product moment pearson correlation as a data analysis technique and used SPSS 2.0 Application as a tool to calculate data. The results showed that among 5 personality dimensions found that Openness is a personality dimension that significantly has a relation with the employee’s OCB of PT Amarta Karya (Persero) Bekasi. There is a significant relation of openness variable 0,377 with significance 0,040 <0,05 to employee’s OCB of PT Amarta Karya (Persero) Bekasi.